Ecología, inserción social y rentabilidad en la explotación de agregados pétreos del área minera "La Victoria" en la Parroquia Malacatos, Cantón Loja - Peña Unda, Alfonso (2016)
The present investigation work "Ecology, Social Insert and Profitability in the Exploitation of Stony Attachés of the mining area "La Victoria" in the parish Malacatos, canton Loja" he/she begins with a sectorial diagnosis of the canton Loja being focused in the exploitation, prosecution and commercialization of stony attaché (arid). To begin with the execution of the investigation plan, the potential market was evaluated through information with respect to the cement consumption provided by entities that control and they register this consumption, since the stony attaché constitutes the indispensable complement of the cement that jointly with formulas and calculations that he carries out the sector of the construction one could obtain real information of the demand of arid in the canton, in what refers to the offer they were carried out surveys to all the bidders, information that was contrasted with the data obtained by entities related with the mining sector. Once obtained these data, you proceeded to project the same ones with the purpose of having a vision to future of the means in which the concession will be unwrapped; for it was adopted it the rate of growth of cement consumption that was determined yearly in 7,95%. Later it proceeds with the Technical Study the same one that details the volume of production of the Concession, the same one that is in capacity of producing 525 m3/day when one works to 100% of installed capacity that it will be starting from the third year of production, this capacity will allow him to cover 43% of the unsatisfied demand (in the third year), because this, enters to the market to compete with price and quality, goal that is guaranteed by the location of the Concession and the characteristics of the material that it generates the mine“La Victoria”. Established the relating data to the market you proceeded to carry out the study of commercialization of the product defined in function of their main uses, requirements and it demands of the industry of the construction, as well as its due price settled down in function of the demand, the competition of similar products and the costs in those that will incur the exploitation of the arid ones, stops later on to derive them to the respective square in function of a guessed right publicity. In the Engineering of the Project the mining technical program of exploitation is detailed whose planned activities will count since with a plan that allows to achieve the exact execution of the outlined objectives, it will be given low technical norms of design, construction and exploitation of quarries as well as the norms of security, hygiene, protection and environmental handling, the same one that will be developed under a legally established artificial organization. With the pertinent information it was developed the later studies to conclude with the Financial Economic Study, the same one that being projected with real data establishes the cost and the profitability of the project, so that, based on this information we takes the final decision on the realization or not of the investment, the same one threw the following information: • The total amount to invest in the project: $ 745.201,18 • Revenue for the first year: $ 620.802,00 • Net Present Value: $ 1.067.863,91 • Recovery Period of capital: 4years, 5 months, 14 days • Internal rate of return: 31,81% • Relation Benefit Cost: 1,94 • Increased costs: 18.09% • Diminution of revenue: 10.50%